"His body is human, but he has a tiracchāna heart": An ethnographic study of the epigenesis of child abuse in Cambodia. (February 2019) - Eisenbruch, Maurice
Abstract: In Cambodia, more than half of all children experience physical, emotional, or sexual abuse. This article examines how Cambodians view the causes and effects of child abuse and analyses its underlying cultural forces. Adopting a conceptual framework originally developed for the cultural context of violence against women, 110 cases of child abuse were ethnographically studied, comprising 61 cases of sexual abuse (50 girls and 11 boys), 26 cases of physical abuse (13 girls and 13 boys), and 23 cases of emotional abuse or neglect (13 girls and 10 boys). The perpetrators included fathers and other close relatives, lay Buddhist officiants and monks, and neighbors. Most informants viewed the sexual or physical abuse of children as stemming from "cultural attractors, " including blighted endowment caused by deeds in a previous life, a bad character starting early in life, astrological vulnerability to abuse, preordained entanglement between the child and the abuser (they are "fated" to meet), sexual craving, "entering the road to ruin, " and a moral blindness that portrays the abuser as blameless. Although these traits are similar to those identified in the explanations of violence against women, there were notable differences such as the role of the tiracchāna in explaining sexual abuse, including incest. Using these findings, this article identifies a cultural epigenesis of child sexual abuse, and provides a blueprint for developing a culturally responsive plan to prevent child abuse.